Workforce professional skills development in times of economic crisis - Popescu, Irina Alina (Management, 2013)
Using unique individual-level data on the continuous professional training courses completed over the period 20072011 this paper addresses a topic a major concern for policy-makers and businesses in the light of the recent transformations emerging markets have suffered during the global financial crisis. The paper presents the analysis of the evolution of the demand for continuous professional training and the changes in the structure of the demand under the circumstances of the economic crisis. Findings reveal a significantly higher demand for continuous professional training for acquiring new qualifications in jobs requiring low educational attainment and competences in foreign languages and information technology in 2008 and 2009, while specializing and performance trainings in qualifications requiring secondary and tertiary education registered a significant increase during 2010 and 2011. More so, the average skill level of professional training is on the rise, demonstrating an increased preference for highly skilled jobs, in the detriment of the low skilled jobs.
Keywords: education; ekonomska kriza; izobraževanje; poklicni razvoj; poklicno usposabljanje; zaposleni